2014
DOI: 10.1063/1.4890578
|View full text |Cite
|
Sign up to set email alerts
|

Effects of layer thickness and alloy composition on carrier lifetimes in mid-wave infrared InAs/InAsSb superlattices

Abstract: Measurements of carrier recombination rates using a time-resolved pump-probe technique are reported for mid-wave infrared InAs/InAs1−xSbx type-2 superlattices (T2SLs). By engineering the layer widths and alloy compositions, a 16 K band-gap of ≃235 ± 10 meV was achieved for all five unintentionally doped T2SLs. Carrier lifetimes were determined by fitting a rate equation model to the density dependent data. Minority carrier lifetimes as long as 10 μs were measured. On the other hand, the Auger rates for all the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
33
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(37 citation statements)
references
References 28 publications
4
33
0
Order By: Relevance
“…Samples are grown by molecular beam epitaxy using previously described techniques [6,9,10,13]. For all seven samples, the epitaxial layers consist of a GaSb buffer layer, a bottom 100-nm Al(As,Sb) barrier layer, an unintentionally doped and nominally 4-μm-thick T2SL absorber layer, a top 100-nm Al(As,Sb) barrier layer, and a 150-nm In(As,Sb) cap layer.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Samples are grown by molecular beam epitaxy using previously described techniques [6,9,10,13]. For all seven samples, the epitaxial layers consist of a GaSb buffer layer, a bottom 100-nm Al(As,Sb) barrier layer, an unintentionally doped and nominally 4-μm-thick T2SL absorber layer, a top 100-nm Al(As,Sb) barrier layer, and a 150-nm In(As,Sb) cap layer.…”
Section: Resultsmentioning
confidence: 99%
“…Temperature-and carrier-density-dependent studies on MWIR InAs=InðAs; SbÞ T2SLs have shown that SRH recombination limits the MC carrier lifetime at low temperatures and low-injection carrier densities [5,6,[8][9][10]13]. The mid-band-gap SRH recombination centers identified in MWIR InAs=InðAs; SbÞ T2SLs have been previously reported to be at an energy approximately 250 meV below the valence-band edge of bulk GaSb [5,9].…”
Section: Introductionmentioning
confidence: 97%
See 2 more Smart Citations
“…A fast, transient increase in differential-transmission signal is observed with a measured response time of 1.4 ps and 2 ps for 2.4 µm and 3.2 µm probe wavelengths, respectively. These timescales characterize the rate at which pump-induced hot carriers thermalize and relax to the band edge 20 . When the probe wavelength continues to increase, the differentialtransmission signal becomes progressively slower, and when the probe wavelength is extended to 4 µm, just above the bandgap, the Pauli-blocking transient persists for nearly 90 ps.…”
mentioning
confidence: 99%